2014
DOI: 10.1016/j.ypmed.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and new-onset diabetes among adult survivors of the World Trade Center disaster

Abstract: This exploratory study found that PTSD, a common 9/11-related health outcome, was a risk factor for self-reported diabetes. Clinicians treating survivors of both the WTC attacks and other disasters should be aware that diabetes may be a long-term consequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 35 publications
2
57
1
Order By: Relevance
“…Cambodians have high rates of untreated mental illness including posttraumatic stress [20,33]. By addressing the role of mental health in diabetes prevention, EWS may be uniquely suited to modify lifestyle factors among Cambodians.…”
Section: Discussionmentioning
confidence: 99%
“…Cambodians have high rates of untreated mental illness including posttraumatic stress [20,33]. By addressing the role of mental health in diabetes prevention, EWS may be uniquely suited to modify lifestyle factors among Cambodians.…”
Section: Discussionmentioning
confidence: 99%
“…Persons with 9/11 exposure, PTSD, or both face increased risk for numerous conditions also associated with smoking (U.S. Department of Health and Human Services, 2014), such as cardiovascular disease (Ahmadi et al, 2011;Boscarino, 2008;Jordan et al, 2011;Jordan et al, 2013;Spitzer et al, 2009), certain cancers (Li et al, 2012;Zeig-Owens et al, 2011), respiratory problems (Brackbill et al, 2009;Maslow et al, 2012;Nair et al, 2012), and diabetes (Agyemang et al, 2012;Boyko et al, 2010;Miller-Archie et al, 2014). The combination of 9/11 exposure and PTSD makes smokers exposed to 9/11 a particularly vulnerable subgroup with increased risk for myriad negative health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22] The presumed mechanism of impact is thought to be mediated by the stress caused by the disaster, which has also been seen in other non-natural disasters. [23][24][25] Our study expands this body of literature by specifically analyzing the acute impact of disasters on diabetic patients by evaluating ED use by diabetic adults after Hurricane Sandy. In our geographic analysis, we found that diabetic adults in evacuation zone level 1 were more likely to have increased the need for post-disaster emergency care.…”
Section: Secondary Diagnosesmentioning
confidence: 92%